2014
DOI: 10.1177/0300985813516648
|View full text |Cite
|
Sign up to set email alerts
|

Pathology of Articular Cartilage and Synovial Membrane From Elbow Joints With and Without Degenerative Joint Disease in Domestic Cats

Abstract: The elbow joint is one of the feline appendicular joints most commonly and severely affected by degenerative joint disease. The macroscopic and histopathological lesions of the elbow joints of 30 adult cats were evaluated immediately after euthanasia. Macroscopic evidence of degenerative joint disease was found in 22 of 30 cats (39 elbow joints) (73.33% cats; 65% elbow joints), and macroscopic cartilage erosion ranged from mild fibrillation to complete ulceration of the hyaline cartilage with exposure of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…However, these conclusions appear to be based on the aetiology of OA in dogs and may not be applicable in the cat. For example, recent information in cats has indicated that they do not appear to suffer from fragmented coronoid process, the most common cause of elbow OA in dogs [ 23 ]. In human patients, obesity is regarded as a predisposing factor for OA [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, these conclusions appear to be based on the aetiology of OA in dogs and may not be applicable in the cat. For example, recent information in cats has indicated that they do not appear to suffer from fragmented coronoid process, the most common cause of elbow OA in dogs [ 23 ]. In human patients, obesity is regarded as a predisposing factor for OA [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…The fastest reparative and regenerative processes take place in tissues with high blood supply (Freire, Meuten, & Lascelles, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The fastest reparative and regenerative processes take place in tissues with high blood supply (Freire, Meuten, & Lascelles, 2014). Saturation of tissues with vascular elements provides a high level of metabolic activity and ability to recover (Beever, Giles, & Meeson, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The cytokines found to be elevated in this study have many potential sources, including peripheral leukocytes or local sources such as monocytes/macrophages, synovial cells, or chondrocytes in the affected joints. While synovitis in degenerative elbow joints in cats has been shown to be relatively mild (Freire et al, 2014), synovitis in OA in people is also typically scored as mild-moderate, and yet there is recognition of the inflammatory component to the disease (Berenbaum, 2013). Toll-like receptor 4 (TLR4) has been particularly implicated in contributing to inflammation in DJD/OA, with increased TLR4 expression in areas of damaged cartilage in patients with OA (Kim et al, 2006).…”
Section: Discussionmentioning
confidence: 99%